Vitamin D deficiency promoting non-24 h sleep–wake disorder: a case report - Radlberger, Richard Friedrich; Kunz, Alexander Baden (Frontiers in Neurology, 2023)
We report a case of an emmetropic woman with excessive daytime sleepiness in alternation with insomnia consistent with the diagnosis criteria of a non-24 h sleep–wake disorder. After being refractory to the usual non-pharmacologic and pharmacologic treatment, we detected a deficiency of vitamin B12, vitamin D3, and folic acid. Substitution of these treatments led to a return of a 24 h sleep–wake rhythm though this remained independent from the external light–dark cycle. The question arises whether the vitamin D deficiency could be regarded as an epiphenomenon or whether there is an up-to-date unknown connection to the inner zeitgeber.